Hermeneutics and Multiplicity of Interpretation - Muhammad Rashid Saeedi (بازیافت)
Hermeneutics has been popular trend to understand philosophical interpretations of distinct texts for centuries. It has been helpful to grasp the comprehension approach of religious, philosophical as well as legal texts.  It is fact about the role of the hermeneutics to manifold literary pieces. hermeneutics deals reciprocated to history, civilization, philosophy and psychology as context and perspective and numerous meanings have been deducted from the triangle of reader, text and recitation. It will be fascinating and interesting to know the role of hermeneutics in Urdu criticism and it varied understanding   of its literature. This research paper will highlight the prime foundation, limits and parameters of hermeneutics for the multiplicity of meaning and interpretation in Urdu criticism would also be examined.